Identifikasi Permasalahan Arsitektur Perpustakaan Umum Daerah Kabupaten Sidoarjo - Putri Astri Rahmadani; Ibrahim Tohar; Rahman Hakim (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
The Regional Public Library of Sidoarjo Regency plays an important role as a public facility in supporting the development of community literacy. Along with population growth and the advancement of the education sector, the library is required to provide spaces that are comfortable, safe, and inclusive for all users. However, existing conditions indicate various architectural problems that potentially hinder the optimal function of the library. This study aims to identify architectural issues at the Regional Public Library of Sidoarjo Regency, including building conditions, spatial layout, user comfort, and the availability of thematic literacy facilities and inclusive spaces. The research method employed observation and literature review. Field observation was conducted to document the actual conditions of the building and library facilities, while the literature review focused on library standards, building regulations, and relevant architectural theories. The results show that although the library building is structurally adequate, the quality of space has not fully met the required standards of comfort, safety, and functionality. The spatial arrangement remains conventional and lacks flexibility, limiting its ability to support diverse literacy activities. In addition, thematic literacy facilities and the application of inclusive design principles are still limited. This study concludes that architectural development efforts are needed, focusing on improving spatial quality, implementing adaptive spatial planning, and providing more diverse and inclusive literacy facilities. The findings are expected to serve as a reference for future development planning of the Regional Public Library of Sidoarjo Regency in order to enhance its role as an educational public space and a community literacy center.